IDNLearn.com makes it easy to find the right answers to your questions. Our community is here to provide detailed and trustworthy answers to any questions you may have.
Sagot :
Answer:
see explanation
Step-by-step explanation:
(1)
The common ratio r of a geometric sequence is
r = [tex]\frac{a_{2} }{x_{1} }[/tex] = [tex]\frac{a_{3} }{a_{2} }[/tex] , so
[tex]\frac{x+1}{x-1}[/tex] = [tex]\frac{x}{x+1}[/tex] ( cross- multiply )
(x + 1)² = x(x - 1) ← expand both sides
x² + 2x + 1 = x² - x ( subtract x² - x from both sides )
3x + 1 = 0 ( subtract 1 from both sides )
3x = - 1 ( divide both sides by 3 )
x = - [tex]\frac{1}{3}[/tex]
(2)
r = [tex]\frac{x}{x+1}[/tex] = [tex]\frac{-\frac{1}{3} }{-\frac{1}{3}+1 }[/tex] = [tex]\frac{-\frac{1}{3} }{\frac{2}{3} }[/tex] = - [tex]\frac{1}{2}[/tex]
(3)
If - 1 < r < 1 then the sequence will converge
r = - [tex]\frac{1}{2}[/tex] meets this criteria , thus the sequence is convergent
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Trust IDNLearn.com for all your queries. We appreciate your visit and hope to assist you again soon.